Water reuse in a circular economy perspective in a microelectronics industry through biological effluents treatments. (20th October 2021) - Ferella, Francesco; Innocenzi, Valentina; Moretti, Giulio; Zueva, Svetlana B.; Pellegrini, Marika; De Michelis, Ida; Ippolito, Nicolò M.; Del Gallo, Maddalena; Prisciandaro, Marina; Vegliò, Francesco
Abstract: The article reports the preliminary results obtained in a pilot plant that treats a spent tetramethylammonium hydroxide (TMAH) solution, a typical chemical compound used in the microelectronics industry and massively present in wastewaters. The plant is based on three aerobic bioreactors in series, fed by a real TMAH solution effluent from the semiconductor industry. The plant ran for 14 days in continuous operating mode with a flow rate of 5 L/h; then, the plant switched to batch mode. The microbial population was analyzed to determine if microbial population changes occurred. The results indicated that TMAH degradation only occurred during the batch operation mode. The TMAH reduction was about 80% in the first reactor and complete (100%) in the second and third bioreactors. At the same time, the microorganisms increased their mass by 338%, 58%, and 1% in the first, second, and third bioreactor, respectively. The degradation intermediates confirmed the efficiency of the process and the possible reuse of water, which closes the water loop's circularity. Furthermore, a nitrate concentration of 150–250 mg/L was found in the last two bioreactors: this implies a significant presence of ammonium-oxidizing bacteria. Community genomic analysis was conducted to detect changes in the microbial community due to changes in operating conditions that could cause reactor failure if methylotrophs were washed out or outcompeted by unspecific bacteria.